Fe+ ion irradiation effects in Fe-10at%Cr films irradiated at 300 °C. (March 2022) - Pantousa, S.; Mergia, K.; Ionescu, A.; Manios, E.; Dellis, S.; Kinane, C.; Langridge, S.; Caruana, A.; Kentsch, U.; Messoloras, S.
Highlights: Fe + ion irradiation of Fe-10at%Cr films at 300 °C. The irradiation produced dose dependent: - lattice constant increase, - grain growth, - Cr depletion in the matrix. These changes occur largely up to 4 displacements per atom (dpa) and afterwards the system attains a dynamic equilibrium. Abstract: Fe-Cr alloys constitute the model systems for the investigation of radiation damage effects in ferritic-martensitic steels which are candidate structural materials for fusion reactors. In the current study Fe-10at%Cr alloy films of 70 nm thickness were irradiated by 490 keV Fe + ions at 300 °C at doses ranging from 0.5 up to 20 displacements per atom (dpa). The Fe + ion energy chosen corresponds to the energy of primary Fe(Cr) knock-on atoms from 14 MeV neutrons. The irradiation effects were investigated employing X-ray diffraction and X-ray and polarized neutron reflectivity. The irradiation produced dose dependent: a) lattice constant increase, b) grain size growth and c) Cr depletion in the matrix. These changes occur largely up to 4 dpa and afterwards the system attains a dynamic equilibrium.